Pregabalin in the management of partial epilepsy - Amir M Arain (Dove Medical Press, 2009)
Amir M ArainVanderbilt University Medical Center, Department of Neurology, Nashville, TN, USAAbstract: Pregabalin is a new antiepileptic medication that works by binding to alpha 2 delta subunit of the voltage-dependent calcium channels present in presynaptic neurons. Its pharmacokinetic advantages include rapid and almost complete absorption, lack of protein binding, linear kinetics, absence of enzyme induction, and absence of interactions with other drugs. Pregabalin was found effective as adjunctive therapy for refractory partial-onset seizures, with up to 51% responder at a dose of 600 mg/day. The lowest effective dose was 150 mg/day. Pregabalin is also approved for treatment of painful diabetic polyneuropathy, postherpetic neuralgia and pain with fibromyalgia. Studies also suggest a beneficial effect on sleep and generalized anxiety disorders. Its main adverse effects in randomized adjunctive trials in adults have been mild to moderate. Most common side effects were dizziness, ataxia, somnolence and diplopia. Weight gain was not prominent in pivotal pregabalin trials, but was more problematic in long-term postmarketing analyses in epilepsy patients. Pregabalin, with its potent antiseizure effect, favorable pharmacokinetic profile, and effectiveness in common co-morbidities is an important addition to the treatment of epilepsy.Keywords: epilepsy, seizures, pregabalin, pharmacology, antiepileptic drugs, tolerability